INTEGRASI TERAPI SANDTRAY DENGAN PENDEKATAN KONSELING BERFOKUS SOLUSI PADA ANAK YANG MENGALAMI TRAUMA - Sugara, Gian Sugiana (JURNAL FOKUS KONSELING, 2017)
Traumatic experience makes a person unhappy and often overwhelmed with excessive fear. They need counseling for relieving the symptoms of the traumatic experienced. Sandtray therapy is a therapeutic technique that utilizes the sandtray as a medium in the therapeutic process. Integration sandtray therapy with solution focused brief counseling approach can help traumatized children to become more adaptive to the symptom of trauma and the purpose of counseling is to increase the resilience. Counselors use questioning techniques to help children traumatized by sandtray therapy with a solution focused approach with the aim of finding exceptions and setting of goals of counseling by the client to overcome the symptom of trauma. Trauma therapy model by integrating solution focused brief counseling with sandtray therapy that consists of creating stabiltas sense of security, reconstructing the trauma story and Â improve relations with the society.